2011
DOI: 10.1016/j.vaccine.2011.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in host antiviral genes: Associations with humoral and cellular immunity to measles vaccine

Abstract: Host antiviral genes are important regulators of antiviral immunity and plausible genetic determinants of immune response heterogeneity after vaccination. We genotyped and analyzed 307 common candidate tagSNPs from 12 antiviral genes in a cohort of 745 schoolchildren immunized with two doses of measles-mumps-rubella vaccine. Associations between SNPs/haplotypes and measles virus-specific immune outcomes were assessed using linear regression methodologies in Caucasians and African-Americans. Genetic variants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 56 publications
(115 reference statements)
3
71
0
Order By: Relevance
“…For example, a non-synonymous rs2229857 (Lys384/Arg) in the antiviral RNA-specific ADAR gene, known to be involved in RNA editing and gene regulation, demonstrated an allele dose-related increase in IL-6 and IFN-γ secretion with the representation of a minor allele. Consistent with the current results, our earlier vaccine study with measles demonstrated an association between ADAR SNP rs2229857 and measles virus-specific IFN-γ ELISPOT responses (Haralambieva et al 2011b). We speculate that this genetic variant is likely to be involved in regulation of virus-induced cellular immune mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…For example, a non-synonymous rs2229857 (Lys384/Arg) in the antiviral RNA-specific ADAR gene, known to be involved in RNA editing and gene regulation, demonstrated an allele dose-related increase in IL-6 and IFN-γ secretion with the representation of a minor allele. Consistent with the current results, our earlier vaccine study with measles demonstrated an association between ADAR SNP rs2229857 and measles virus-specific IFN-γ ELISPOT responses (Haralambieva et al 2011b). We speculate that this genetic variant is likely to be involved in regulation of virus-induced cellular immune mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Recent advances in examining the association of immune response between "high" and "low" responders to vaccines with genotype differences have emphasized the role of genetic make-up in vaccine response. [22][23][24][25] Race may serve as a proxy for these genetic differences. The clinical significance of this finding is unclear, however, because race was not significantly associated with the more clinically relevant outcome of seroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these three SNPs (rs2229857, rs1127317) were also associated with variations in cytokine secretion after measles stimulation. (Haralambieva et al 2011) The non-synonymous SNP, rs2229857 encoding a K>R change, is also associated with sustained response to IFN therapy for chronic HCV infection. (Hwang et al 2006; Welzel et al 2009)…”
Section: Discussionmentioning
confidence: 99%